2014
DOI: 10.1016/j.triboint.2013.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The role of lubricant feeding conditions on the performance improvement and friction reduction of journal bearings

Abstract: Most conventional hydrodynamic journal bearing performance tools cannot suitably assess the effect of lubricant feeding conditions on bearing performance, even though these conditions are known to affect important performance parameters such as eccentricity and power loss. A thermohydrodynamic analysis suitable to deal with realistic feeding conditions has been proposed. Special attention was given to the treatment of phenomena taking place within grooves and their vicinity, as well as to the ruptured film reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…The bearing analysis tools is the same as the one already described in previous works [16] [20]. Therefore, only a brief outline of the model is now provided.…”
Section: Theoretical Model Outlinementioning
confidence: 99%
“…The bearing analysis tools is the same as the one already described in previous works [16] [20]. Therefore, only a brief outline of the model is now provided.…”
Section: Theoretical Model Outlinementioning
confidence: 99%
“…This mixing model, sketched in Figure 5(b), has already been detailed in a recent publication. 3 It relates the feeding temperature, the inner temperature of the groove, "…”
Section: Thermal Modelmentioning
confidence: 99%
“…And the effects of lubricant feeding pressure and temperature on bearing performance have been analyzed. 17 In fact, the above researches have carried out a series of valuable theoretical and experimental works on these journal bearings. However, the experimental studies focused on the industrial application of hydrodynamic journal bearing reported in the literature are scarce, especially in the monitoring of HLFCs.…”
Section: Introductionmentioning
confidence: 99%